Prevalence and genetic aspects of deaf mutism in Shanghai. Issue 10 (October 1987) - Hu, D N; Qiu, W Q; Wu, B T; Fang, L Z; Zhou, F; Gu, Y P; Zhang, Q H; Yan, J H
Abstract : Two hundred and eighty-five cases of congenital deaf mutism were ascertained in a population of 483, 611 in Zhabei District in Shanghai. The prevalence was 0.059% (1:1697). Inherited cases accounted for 84.83% of all cases. The mode of inheritance was autosomal recessive with complete penetrance and heterogeneity (consisting of at least five different loci). The fitness was 77.63%, the coefficient of selection was 0.2237, the mutation rate was 1.119 x 10(-4) mutation/gamete, and no heterozygote advantage was proven.